2004
DOI: 10.1152/ajpheart.00022.2003
|View full text |Cite
|
Sign up to set email alerts
|

Responses of chronically hypoxic rat hearts to ischemia: KATP channel blockade does not abolish increased RV tolerance to ischemia

Abstract: Responses of chronically hypoxic rat hearts to ischemia: KATP channel blockade does not abolish increased RV tolerance to ischemia. Am J Physiol Heart Circ Physiol 286: H545-H551, 2004. First published October 9, 2003 10.1152/ajpheart.00022.2003.-Chronic hypoxia may precondition the myocardium and protect from ischemia-reperfusion damage. We therefore examined the recovery of left and right ventricular function after ischemia and reperfusion (15 min each) in isolated blood-perfused working hearts from normoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…The beneficial effects of chronic hypoxia were found on both ventricles (31). In contrast, 14 days of sustained hypoxia in adult rats protected RV from ischemia-reperfusion damage but failed to improve postischemic LV function (21). In the present study, we show a cardioprotection developed in the papillary muscle of the LV from adult rats during sustained hypobaric hypoxia, provided that the duration of the exposure is long enough.…”
Section: Discussionmentioning
confidence: 42%
“…The beneficial effects of chronic hypoxia were found on both ventricles (31). In contrast, 14 days of sustained hypoxia in adult rats protected RV from ischemia-reperfusion damage but failed to improve postischemic LV function (21). In the present study, we show a cardioprotection developed in the papillary muscle of the LV from adult rats during sustained hypobaric hypoxia, provided that the duration of the exposure is long enough.…”
Section: Discussionmentioning
confidence: 42%
“…This is consistent with observations showing that the activation of mitochondrial K ATP channels increases ROS generation, which subsequently activates prosurvival signaling pathways and inhibits MPTP opening during myocardial I/R (6, 18, 35, 38). However, mitochondrial K ATP channels might not participate in the cardioprotection of right ventricular function induced by chronic hypoxia in rats (9). Other ROS-producing enzymes, e.g., NADPH oxidase and xanthine oxidase, have also been proposed to participate in cardioprotection (10,25).…”
Section: Mitochondria As the Main Source Of Ros In Ihh-induced Cardiomentioning
confidence: 99%
“…In an experimental study in the working heart, it was found that chronic hypoxia improved postischemic RV, not LV, function. This mechanism was independent of K ATP channels [5]. As opposed to these findings, a study in isolated cardiomyocytes subjected to 15 min of hypoxia as a preconditioning stimulus before a 60-min period of sustained hypoxia demonstrated an increased LDH release in cardiomyocytes from the RV compared to LV.…”
Section: Discussionmentioning
confidence: 99%